Knowledge Among School Students Regarding Selected Common Preventable Diseases - Ali, ASM Zulfiquer (Sir Salimullah Medical College Journal, 2022)
Introduction: The health of school children is a common concern of the school, parents and the community. A child has to be healthy to learn and the school is an important place, next to home, where a child learns to be healthy. The schools are particularly important because these institutions represent gathering places for population of age 5-17 years. They are susceptible to many communicable diseases and vulnerable to physical, mental and moral hazards. Objective: To assess the level of knowledge of school students regarding selected common preventable diseases. Methods and Materials: This descriptive cross-sectional study was conducted from January 2019- June 2019 among purposively selected 101 students of class IX and X of Cantonment Public School and Millennium Star School, Rangpur Cantonment. Data were collected through face to face interview using pre-tested structured questionnaire. Data were checked for quality control and analyzed by computer by using SPSS software. Results: Mean age of the respondent was 14.68 ± 0.24 years. Among the participants maximum 77.2% were in the 13-15 years age group, followed by 22.8% were in the age group of 16-18 years, Male were 55.5% and female 44.5%. Majority of the respondents 51.5% from class X and rest 48.5% from class IX. Out of total 101 respondents 40.0% belonged to Good knowledge, 50.0% average and 10.0% were poor knowledge (Table-IV). Association between mean score of knowledge and age, sex, educational status and monthly family income found statistically significant (p<0.05) (Table-V). Conclusion: The study revealed that 40.0% of respondent had ‘good knowledge’,50.0% had ‘Average knowledge’, and 10.0% had ‘poor knowledge’ regarding preventable disease. Sir Salimullah Med Coll J 2022; 30: 40-45